Null strain analysis of submerged aneurysm analogues using a novel 3D stereomicroscopy device. Issue 8 (10th June 2020) - Lane, Brooks A.; Lessner, Susan M.; Vyavahare, Narendra R.; Sutton, Michael A.; Eberth, John F.
Abstract: To measure the inhomogeneous 3D-strain fields present during inflation-extension testing of physiologically submerged micro-aneurysms, a Stereo Digital Image Correlation (StereoDIC) microscopy system is developed that revolves 15 ° stereo-angle cameras around a centrally-mounted target. Calibration is performed using submerged dot patterns and system accuracy verified using strain and deformation analyses for rigid body motions of speckle-patterned, micro-aneurysmal surrogates. In terms of the Green-Lagrange strain tensor and the 3D displacement fields, the results are stable even after 120 minutes, with maxima in both strain bias and strain standard deviation less than 2E-03 for all components, and micron-level displacement standard deviation.